Fashion Killa : how hip-hop revolutionized high fashion - Krishnamurthy, Sowmya (Gallery Books, an imprint of Simon & Schuster, Inc., 2023)
"A cinematic narrative of glamour, grit, luxury, and luck, Fashion Killa draws on exclusive interviews with the leaders of the fashion world to tell the story of the hip-hop artists, designers, stylists, and unsung heroes who fought the power and reinvented style around the world over the last fifty years. Set in the sartorial scenes of New York, Paris, and Milan, journalist Sowmya Krishnamurthy's reporting on the intersecting histories of hip-hop and contemporary fashion focuses on the risk takers and rebels--the artists, designers, stylists, models, and tastemakers--who challenged a systemic power structure and historically reinvented the world of haute couture. Fashion Killa is a classic tale of a modern renaissance; of an exclusionary industry gate-crashed by innovators; of impresarios--Sean "Diddy" Combs, Dapper Dan, Virgil Abloh--hoisting hip-hop from the streets to the stratosphere; of supernovas--Lil' Kim, Cardi B, and Megan Thee Stallion--allying with kingmakers--Anna Wintour, Donatella Versace, and Ralph Lauren; of traditionalist fashion houses--Louis Vuitton, Fendi, and Saint Laurent--transformed into temples of rap gods like Kanye West, Nicki Minaj, and Travis Scott. Krishnamurthy explores the connections between the DIY hip-hop scene and the exclusive upper-echelons of high fashion. She tracks the influence of music and streetwear on the most exclusive (and exclusionary) luxury brands. At the intersection of cultural commentary and oral history, Fashion Killa commemorates the contributions of hip-hop to music, fashion, and our culture at large"--